Community-Based Implementation of a Waterwheel-Based Micro-Hydro Power System through Civil Water Intake Construction in Rural Agam, Indonesia - Faisal Ashar; Yaumal Arbi; Ricky Maulana; Risma Apdeni (Universitas Negeri Padang, 2025)
This article reports on a community service program to implement a waterwheel-based micro-hydro power system by constructing a civil water intake in Nagari Kamang Hilia, Agam Regency, West Sumatra. The program aimed to provide renewable electricity for rice milling and community street lighting, while strengthening local capacity for operations and maintenance. The implementation consisted of stakeholder coordination, field surveys, drone-based mapping, preparation of Detailed Engineering Design, civil intake construction, electrical integration, commissioning, and community training. The constructed components included an intake structure, a guide channel, a sluice gate, a trash rack, inlet and outlet channels, and a waterwheel chamber. These components were designed to regulate water flow, minimize disturbance from sediment and debris, and support stable waterwheel operation under low-head conditions. Field measurements indicated an average flow velocity of approximately 2 m/s, supporting an initial system capacity of about 5 kW. The system provides renewable electricity for productive use and street lighting, reducing dependence on costly diesel fuel and improving local energy resilience. The training activities also improved community knowledge of intake cleaning, sediment control, waterwheel inspection, and basic electrical safety. The program demonstrates that integrating civil engineering infrastructure, renewable energy technologies, and community participation can serve as a practical model for sustainable rural development.